2022
DOI: 10.3390/jcdd9030079
|View full text |Cite
|
Sign up to set email alerts
|

A Case Series of Concomitant Cardiac Electrical Disease among Takotsubo Syndrome Patients and Literature Review

Abstract: The pathophysiology of Takotsubo Syndrome (TTS) is not completely understood and the trigger of sudden cardiac death (SCD) in TTS is not clear either. We therefore sought to find an association between TTS and primary electrical diseases. A total of 148 TTS patients were analyzed between 2003 and 2017 in a bi-centric manner. Additionally, a literature review was performed. The patients were included in an ongoing retrospective cohort database. The coexistence of TTS and primary electrical diseases was confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…A recent retrospective review study reported that among 148 TTS patients, coexistence of TTS and primary electrical diseases was confirmed in 5 cases; catecholaminergic polymorphic VT (n = 1, 18-year-old female), long QT syndrome 1 (LQTS 1) (n = 2, 72-year-old female and 65-year-old female), LQTS 2 (n = 1, 17-year-old female), and LQTS in the absence of mutations (22-year-old female). 72 After TTS, 4 patients suffered from malignant tachyarrhythmia and recurrent syncope. A subcutaneous ICD was implanted in 3 of these patients.…”
Section: In-hospital Cardiac Arrestmentioning
confidence: 99%
“…A recent retrospective review study reported that among 148 TTS patients, coexistence of TTS and primary electrical diseases was confirmed in 5 cases; catecholaminergic polymorphic VT (n = 1, 18-year-old female), long QT syndrome 1 (LQTS 1) (n = 2, 72-year-old female and 65-year-old female), LQTS 2 (n = 1, 17-year-old female), and LQTS in the absence of mutations (22-year-old female). 72 After TTS, 4 patients suffered from malignant tachyarrhythmia and recurrent syncope. A subcutaneous ICD was implanted in 3 of these patients.…”
Section: In-hospital Cardiac Arrestmentioning
confidence: 99%